Extracellular traps derived from macrophages, mast cells, eosinophils and neutrophils are generated in a time‐dependent manner during atherothrombosis. Issue 4 (25th January 2019) - Pertiwi, Kartika R; de Boer, Onno J; Mackaaij, Claire; Pabittei, Dara R; de Winter, Robbert J; Li, Xiaofei; van der Wal, Allard C
Abstract: Extracellular traps generated by neutrophils contribute to thrombus progression in coronary atherosclerotic plaques. It is not known whether other inflammatory cell types in coronary atherosclerotic plaque or thrombus also release extracellular traps. We investigated their formation by macrophages, mast cells, and eosinophils in human coronary atherosclerosis, and in relation to the age of thrombus of myocardial infarction patients. Coronary arteries with thrombosed or intact plaques were retrieved from patients who died from myocardial infarction. In addition, thrombectomy specimens from patients with myocardial infarction were classified histologically as fresh, lytic or organised. Neutrophil and macrophage extracellular traps were identified using sequential triple immunostaining of CD68, myeloperoxidase, and citrullinated histone H3. Eosinophil and mast cell extracellular traps were visualised using double immunostaining for eosinophil major basic protein or tryptase, respectively, and citrullinated histone H3. Single‐ and double‐stained immunopositive cells in the plaque, adjacent adventitia, and thrombus were counted. All types of leucocyte‐derived extracellular traps were present in all thrombosed plaques, and in all types of the in vivo‐ derived thrombi, but only to a much lower extent in intact plaques. Neutrophil traps, followed by macrophage traps, were the most prominent types in the autopsy series of atherothrombotic plaques, including the adventitia adjacent to thrombosed plaques. In contrast, macrophage traps were more numerous than neutrophil traps in intact plaques (lipid cores) and organised thrombi. Mast cell and eosinophil extracellular traps were also present, but sparse in all instances. In conclusion, not only neutrophils but also macrophages, eosinophils, and mast cells are sources of etosis involved in evolving coronary thrombosis. Neutrophil traps dominate numerically in early thrombosis and macrophage traps in late (organising) thrombosis, implying that together they span all the stages of thrombus progression and maturation. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.